Value chain of cabbage in Bukidnon and Kapatagan net margins, market options and price analysis - Castro, Miko Mariz C.; Digal, Larry N.
This study looks into the cabbage chain in Brgy. Kapatagan, Davao del Sur and Bukidnon. The objective in general was to compare the profitability of the farmers according to their location and their choice of market channels, using net margin analysis. Specifically, the study documented the supply chains in both areas and the issues that go along with the chains, evaluated the existing chains, identified enhancements, identified which among the nodes gained the highest margins, and determined how prices are formed. Results showed that in Kapatagan, the farmers who supply directly to Davao City receive the highest margins. On the other hand, wholesalers in CDO receive the highest margins among the other chain nodes. The factors that can influence the price of cabbage are: (1) the market structure, (2) access to market information, and (3) distance to the market. Price analysis was based on chain actors' perception and researcher's observations. The study found that wholesalers influence the prices of cabbage in Kapatagan, Davao del Sur and in Cagayan de Oro City.
Thesis, Undergraduate (BS Agribusiness Economics) -- University of the Philippines, Mindanao